VD_FINDINFO HC / 2011 / 199 vom 9. März 2011 - VD Tribunal cantonal (2011)
CONTRAT DE TRAVAIL, RÉSILIATION, ACCORD DE VOLONTÉS, CONTRAT DE DURÉE DÉTERMINÉE | 115 CO, 18 CO, 334 al. 1 CO, 451 CPC, 452 al. 2 CPC, 465 al. 1 CPC, 46 al. 1 LJT, 46 al. 2 LJT, 405 al. 1 CPC (CH)